The Scientific Revolution of Thomas Kuhn and Their Relevances for Humanization of Islamic Law - Muhamad Ali Mustofa Kamal (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2016)
This paper tries to explore the views of Thomas Kuhn that science is moving through the stages that will culminate in normal conditions and then